Between tradition and avant-garde, an analysis of the documentary film Antonio Gaudí (1984): Teshigahara Hiroshi and Takemitsu Tōru - Sastre, Griselda Vilar (Mirai. Estudios Japoneses, 2021)
This research focuses on the audiovisual analysis of the documentary film Antonio Gaudí (1984), directed by the Japanese filmmaker Teshigahara Hiroshi (Tokyo, January 28, 1927 - Tokyo, April 14, 2001). This film is an important example of the artistic relationship between the director and the Japanese musician Takemitsu Tōru (Tokyo, October 8, 1930 - Tokyo, February 20, 1996), composer of important soundtracks of Japanese cinematography. The particular portrait of the architectural work of Antonio Gaudí (Reus, June 25, 1852 - Barcelona, ​​June 10, 1926) and Barcelona showed on this documentary is interesting to assess the details of this film, focusing on the narrative and musical features.